Long intergenic non-coding RNAs have an independent impact on survival in multiple myeloma. Issue 12 (December 2018) - Samur, Mehmet; Minvielle, Stephane; Gulla, Annamaria; Fulciniti, Mariateresa; Cleynen, Alice; Aktas Samur, Anil; Szalat, Raphael; Shammas, Masood; Magrangeas, Florence; Tai, Yu-Tzu; Auclair, Daniel; Keats, Jonathan; et al.
Abstract Although long intergenic non-coding RNAs (lincRNA) role in various cancers is described, their significance in Multiple Myeloma (MM) remains poorly defined. Here we have studied the lincRNA profile and their clinical impact in MM. We performed RNA-seq on MM cells from 308 newly diagnosed and uniformly treated patients, 16 normal plasma cells and utilized RNA-seq data from 532 newly diagnosed patients from CoMMpass study to analyze for lincRNAs. We observed 869 differentially expressed lincRNAs in MM compared to normal plasma cells. We identified 14 lincRNAs associated with PFS and calculated a risk score to stratify patients. The median PFS between high vs low-risk groups was 17 months vs not-reached (NR); and OS 30 months vs NR, respectively (p < 0.0001 for both). In the independent validation dataset between high and low-risk groups, PFS was 27 vs 42 months (HR 2.06 [1.44−2.96];p < 0.0005); and 4-year OS 62% vs 86% (HR 2.76 [1.51–5.05];p < 0.0005) confirming significant clinical relevance of lincRNA in MM. Importantly, lincRNA signature was able to further identify patients with significant differential outcomes within each low and high-risk categories identified using standard risk categorization including cytogenetic/FISH, ISS, and MRD negative or positive. Our results suggest that lincRNAs have an independent effect on MM outcome and provide a rationale to evaluate its molecular and biological impact.